1992
DOI: 10.1165/ajrcmb/6.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Regulation of Transforming Growth Factor-β mRNA in Rat Lung Fibroblasts

Abstract: Pulmonary fibrosis is a well-known toxic response to bleomycin treatment. Here we demonstrate the direct effects of bleomycin on lung fibroblasts that resulted in a marked increase of collagen synthesis as compared with total noncollagen protein synthesis. Bleomycin treatment of rat lung fibroblast cultures resulted in an increase of total cellular transforming growth factor-beta (TGF-beta) mRNA and increased secretion of TGF-beta protein into the conditioned media. beta 2-Microglobulin was measured as an mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 34 publications
6
49
0
Order By: Relevance
“…A recent study showed that TGF␤ is a mediator of the fibrotic effect of bleomycin at the transcriptional level and that the TGF␤ response element is required for bleomycin stimulation of the pro␣1(I) collagen promoter (30). These previously published results (27)(28)(29)(30) indicate that bleomycin increases extracellular matrix production even without the involvement of immune cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A recent study showed that TGF␤ is a mediator of the fibrotic effect of bleomycin at the transcriptional level and that the TGF␤ response element is required for bleomycin stimulation of the pro␣1(I) collagen promoter (30). These previously published results (27)(28)(29)(30) indicate that bleomycin increases extracellular matrix production even without the involvement of immune cells.…”
Section: Discussionsupporting
confidence: 70%
“…It was shown that bleomycin up-regulates type I collagen and fibronectin mRNA in cultured normal skin fibroblasts (28). Exposure of rat lung fibroblast cultures to bleomycin results in elevated TGF␤ mRNA synthesis and TGF␤ protein, which is followed by increased procollagen gene transcription (29). A recent study showed that TGF␤ is a mediator of the fibrotic effect of bleomycin at the transcriptional level and that the TGF␤ response element is required for bleomycin stimulation of the pro␣1(I) collagen promoter (30).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cytokines have been implicated, such as IL-1 [13,14], TNF-␣ [15], and TFG-␤ [24]. Lung macrophages have been reported as the primary source of these cytokines [13][14][15][16][17][18][19][20][21][22], but other cell types such as fibroblasts [23], eosinophils [18], and endothelial cells [24] also have been shown to secrete TGF-␤ after BLM stimulation. In addition to TGF-␤, the pleiotropic cytokine TNF-␣ also promotes the growth of fibroblasts [36].…”
Section: Discussionmentioning
confidence: 99%
“…Through its fibroblast-stimulating properties [22], TGF-β may play a role in granuloma formation [23]as well as in the resolution of inflammation [24]. Because TGF-β is known to be secreted in an inactive form, it was no surprise that there was no bioactivity in any SN.…”
Section: Discussionmentioning
confidence: 99%